2001
DOI: 10.1037/0003-066x.56.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Family psychology and family therapy in Japan.

Abstract: The development of family psychology and family therapy in Japan has occurred mostly since the 1980s. This development was originally activated by the major social issue in contemporary Japan of school refusal, in which more than 127,000 children either overtly refuse to or claim that they cannot go to school. From a family perspective, this problem is analyzed as it relates to the confusion that children experience from unbalanced and unclear boundaries in family relations or "membranes." An approach to famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Beneath the cultural differences that we have emphasized lie important similarities between Japan and the West in both attachment and family systems dynamics. For example, there are clinical reports that Japanese children who suffer from school phobia have family patterns like those described in the West—extremely high levels of mother‐child closeness and avoidance by fathers (Kameguchi & Murphy‐Shigematsu, 2001). While we believe that this pattern is more common and more adaptive in Japan than in the West, the clinical reports suggest that, even in Japan, the most severe instances of this family pattern may be associated with problems that are similar to those it engenders in the West.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beneath the cultural differences that we have emphasized lie important similarities between Japan and the West in both attachment and family systems dynamics. For example, there are clinical reports that Japanese children who suffer from school phobia have family patterns like those described in the West—extremely high levels of mother‐child closeness and avoidance by fathers (Kameguchi & Murphy‐Shigematsu, 2001). While we believe that this pattern is more common and more adaptive in Japan than in the West, the clinical reports suggest that, even in Japan, the most severe instances of this family pattern may be associated with problems that are similar to those it engenders in the West.…”
Section: Resultsmentioning
confidence: 99%
“…The dialectic of similarity and difference does not end there. Close examination of these similarities in family patterns associated with school phobia leads to the detection of yet other differences: Japanese clinicians maintain that school phobia is manifested by “good children who want to go to school,” (Kameguchi & Murphy‐Shigematsu, 2001, p. 66), they suggest that “mothers' overinvolvement in their children's lives may be a way of freeing the fathers to work,” (p. 67), and they partially attribute the children's refusal to their natural desire to have their dependency needs indulged by their mothers—“a psychological concept referred to in Japanese as amae ” (p. 67). Western experts are less likely to explain school refusal in these ways (indeed, there is no exact counterpart to amae in the West).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the problems referred to as "school refusal" and "truancy" be regarded collectively as "school refusal behavior" (e.g., Kearney, 2003;Lyon & Cotler, 2007). Others maintain the distinction between school refusal and truancy (e.g., Elliott & Place, 2012;Goodman & Scott, 2012;Havik, Bru, & Ertesvåg, 2015a;Hella & Bernstein, 2012;Heyne, Sauter, & Maynard, 2015;Torrens Salemi & McCormack Brown, 2003).…”
mentioning
confidence: 99%
“…As Kameguchi and Murphy-Shigematsu (2001) explain, much of the impetus for the growth of these fields since the early 1980s was provided by the increased awareness of serious problems afflicting Japanese youth. The ineffectiveness of traditional psychotherapeutic approaches in resolving such problems led to more interest among professionals in family therapy.…”
Section: The Emergence Of Family Counseling In Japanmentioning
confidence: 97%